Architecture and Large Industrial Buildings of the City of Navoi - Xikmatova Baxora (Zien Journals, 2022)
This article describes the full compliance of the city of Navoi with the requirements of modern urban planning, which includes industrial zones, residential areas, public and residential buildings and landscape solutions that provide the best conditions for people to work and relax
Keywords: Urban planning; modernity; ecology; industrial zones